Diagnostic and prognostic value of gingival fluid examination in patients with catarrhal gingivitis - Gutierrez H. Walker, Ortiz N. Hall (Open Journal of Physicians and Surgeons, 2025)
Original Article OJPS, 2025; Volume 7 (5): 11-20 Gingival fluid, which characterizes the condition of periodontal tissues, is also the first element of the immune defense of the tooth as an organ. Recent studies have shown that one of the important components of the development of inflammatory processes in periodontal tissues is a violation of the processes of intercellular interaction with the participation of cytokines or immunoregulatory mechanisms at the level of the gingival junction. It has been suggested that changes in the interaction in the local network of cytokines accompany an exacerbation of the inflammatory process in the periodontium. At present, indications for carrying out preventive hygiene measures using the above methods have not been developed; there is no justification or objective criteria for assessing the need for repeated courses in healthy people and in people with varying degrees of severity of periodontal diseases. Along with this, there is insufficient data on changes in the immunoregulatory parameters of the gingival fluid against the background of professional oral hygiene. A study of the cytological and cytokine composition of the gingival fluid in healthy people and in people with periodontal diseases of varying severity before and after ultrasonic treatment using the Piezon Master 400 device and teeth cleaning using the Air-Flow sandblasting method will allow developing an examination algorithm for oral hygiene disorders. The aim of this study was to determine the diagnostic and prognostic value of changes in the cytological composition and cytokine profile of gingival fluid in patients with inflammatory periodontal diseases during professional oral hygiene and to substantiate the optimal timing of its repeated courses.